Pengaruh Pemberian Insentif, Lingkungan Kerja dan Kepemimpinan Terhadap Kinerja Pegawai RSUD Benyamin Guluh Kolaka Sulawesi Tenggara - Irma, Irma; Basalamah, Salim; Zakaria, Junaiddin (Innovative: Journal Of Social Science Research, 2024)
Abstract This study aims to investigate and analyze the influence of incentives, work environment, and leadership on the performance of employees at RSUD Benyamin Guluh Kolaka, Southeast Sulawesi. The target population of this research comprises 72 individuals associated with Employee Performance, all of whom served as respondents, using a Multiple Linear Regression analysis model The study's results indicate that all variables namely, incentives, work environment, and leadership have a positive and significant simultaneous effect on the Employee Performance at RSUD Benyamin Guluh Kolaka, Southeast Sulawesi. Meanwhile, on a partial basis, the work environment factor was found to have the most dominant significant influence on Employee Performance at RSUD Benyamin Guluh Kolaka, Southeast Sulawesi. Keywords: Incentives, Work Engagement, Leadership, Employee Performance